The Effect Extender of Young Coconut Water in 0,9% Sodium Chloride On Sperm Quality catfish (Hemibagrus nemurus) During Storage - Hari Devianti; Hamdan Alawi; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study aimed to evaluete the effect of extender coconut water and NaCl on sperm motility, viability, and fertility of riverine bagrid catfish (Hemibagrus nemurus) storage. This experiment used Completely Randomized Design (CRD) with 5 treatments and 3 replications, namely Treatment P0: 0.1 ml sperm plus coconut water 0% + NaCl 100%, P1: 0.1 ml sperm plus coconut water 40 % + NaCl 60%, P2: 0.1 ml sperm plus coconut water 50% + NaCl 50%, P3 0.1 ml sperm plus coconut water 60 % + NaCl 40%, and P4 0.1 ml sperm plus coconut water 70 % + NaCl 70%. The results showed that the addition of coconut water and NaCl on sperm storage significantly affect sperm quality of catfish and during 96 hours of storage. The result showed that the best quality sperm of catfish treated by P2 was higher than (P<0,05) other treatment. In addition, the optimal storage time was in 48 hours, because it had very good motility and highest viability (63,861%). But after 96 hours in storage, fertility decrease until 21,80%.Keywords: Hemibagrus nemurus, coconut water, spermatozoa